Comparative Study of Ant Abundance in Disturbed and Undisturbed Areas of Patna Zoo, an Urban Environment - Sinha, Ranjita; Singh, C.V.; Kumar, Vijay (American Journal of Biodiversity, 2026)
Zoo in the urban area are increasingly recognized not only for their social and economic benefits but also for their potential to conserve biodiversity. In addition to conservation of biodiversity, zoo reconnect people with nature and create habitat for a wealth of organisms (Goddard s., 2010). Moreover, some of these organism acts as ecosystem monitor and contribute valuable eco- system services such as pollination, decomposition, pest control, aeration in soil and nutrient cycling. Despite their modest size, urban insects like ants may be quite important to the biodiversity of zoo. This study, conducted in the fast-growing Indian city of Patna, evaluates the distribution, variety, and quantity of ants in tropical urban zoo. Pitfall traps and manual collecting were used in the study of the Patna Zoo. In both the damaged and undisturbed areas of the zoo, we counted a lot of ants. We discovered a variety of ant species, and the number of ant species we saw was strongly correlated with the number of types of trees and shrubs. The variety and quantity of ant species were also impacted by zoo management techniques. As a result, areas with less aggressive weeding techniques and a higher percentage of undisturbed space compared to disturbed area showed higher insect counts. In this study, we examined the impact of disturbance on ant diversity and richness in zoo. Specifically, we evaluated how factors such as soil texture, tillage practices, and proximity to natural habitats influence ant diversity.